Designing healthier and acceptable diets using data envelopment analysis. Issue 13 (17th September 2020) - Kanellopoulos, Argyris; Gerdessen, Johanna C; Ivancic, Ante; Geleijnse, Johanna M; Bloemhof-Ruwaard, Jacqueline M; van't Veer, Pieter
Abstract: Objective: The objective of this research is to propose methodology that can be used to benchmark current diets based on their nutrient intakes and to provide guidelines for improving less healthy diets in a way that is acceptable for the studied population. Design: We discuss important limitations of current diet models that use optimisation techniques to design healthier and acceptable diets. We illustrate how data envelopment analysis could be used to overcome such limitations, and we describe mathematical models that can be used to calculate not only healthier but also acceptable diets. Setting: We used data from the Nutrition Questionnaires plus dataset of habitual diets of a general population of adult men and women in The Netherlands ( n 1735). Participants: Adult population. Results: We calculated healthier diets with substantial higher intakes of protein, fibre, Fe, Ca, K, Mg and vitamins, and substantially lower intakes of Na, saturated fats and added sugars. The calculated diets are combinations of current diets of individuals that belong to the same age/gender group and comprise of food item intakes in proportions observed in the sample. Conclusions: The proposed methodology enables the benchmarking of existing diets and provides a framework for proposing healthier alternative diets that resemble the current diet in terms of foods intake as much as possible.